1975
DOI: 10.1021/i360056a011
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Hydrazine on Shell 405 Catalyst at High Pressure

Abstract: The investigation of the decomposition of hydrazine on Shell 405 (iridium-on-alumina catalyst) was extended to a pressure of 9100 psi. The ammonia concentration in the products increased with increasing pressure in a manner consistent with the data reported earlier (Wood and Bryant, 1973) for lower pressures (500-5050 psi). Based on a two-step mechanism for the reaction N2H4 -%NH3 + 1/3n2; nH3 -*• (1 -X)NH3 + 1/2XN2 + %XH2, the fraction (X) of the ammonia dissociated decreased to a value of 0.532 at 9100 psi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Both conventional (Grossweiner et al, 1963;Grossweiner a n d Usui, 1971;Santus and Grossweiner, 1972;Subramanyan and Tollin, 1972;Pailthorpe et al, 1973;Templer and Thistlethwaite, 1976) and laser flash photolysis (Bent and Hayon, 1975;Bryant et al, 1975;Baugher and Grossweiner, 1977;Volkert etal., 1977) have been extensively used to investigate the solution phase photophysics of Trp and its derivatives. In these experiments transient absorption spectra in H 2 0 of e; , (A, , , = 650 nm), the radical cation.…”
Section: Tryptophan Photoionizationmentioning
confidence: 99%
“…Both conventional (Grossweiner et al, 1963;Grossweiner a n d Usui, 1971;Santus and Grossweiner, 1972;Subramanyan and Tollin, 1972;Pailthorpe et al, 1973;Templer and Thistlethwaite, 1976) and laser flash photolysis (Bent and Hayon, 1975;Bryant et al, 1975;Baugher and Grossweiner, 1977;Volkert etal., 1977) have been extensively used to investigate the solution phase photophysics of Trp and its derivatives. In these experiments transient absorption spectra in H 2 0 of e; , (A, , , = 650 nm), the radical cation.…”
Section: Tryptophan Photoionizationmentioning
confidence: 99%
“…However, around 86% of English learners (ELs) do not demonstrate proficiency in mathematics, despite federal and state requirements to meet their academic needs (National Center for Education Statistics [NCES], 2013). Difficulties in solving word problems are evident in students' reading comprehension, understanding the problem's meaning, and performing multiple steps to solve them (Bryant et al, 2019). Mayer (1998) indicated that students need five types of knowledge to solve word problems: linguistic, which refers to understanding English language and syntax; semantic, which represents understanding the meanings of words; schematic, which denotes specific knowledge of word problem types and disregarding irrelevant information; strategic, which signifies the ability to plan and monitor solution strategies; and procedural, which indicates the ability to perform a sequence of operations.…”
Section: Introductionmentioning
confidence: 99%
“…Problem solving is a crucial aspect of mathematics education in schools that involves complex processes and multiple types of knowledge and skills (National Council of Teachers of Mathematics [NCTM], 2000). To solve mathematical word problems, students need to comprehend the problem structures and translate them into mathematical equations (Bryant et al, 2019). Developing strong word problem-solving (WPS) skills can improve academic success, foster positive relationships with peers, and increase the likelihood of pursuing higher-paying jobs after high school (Fuchs et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the need of developing an inclusive education for all students, it is important to promote actions and strategies that can develop a quality and equitable education, and therefore, this research focuses on the search for inclusive strategies for students with SEN, since research is in a way lacking on how to generate inclusive actions and strategies within the ordinary classroom (Bryant, Bryant, and Smith, 2019; Golder et al, 2005; Mitchell, 2004; Paju, Räty, Pirttimaa, and Kontu, 2016; Robinson, 2017).…”
Section: Introductionmentioning
confidence: 99%